The Influence of Culture on the Translation Process of Cultural Terms and Expressions in English Novels into Indonesian - Rosdiana Rajagukguk (Manunggal Halim Jaya, 2026)
Research on the translation of cultural terms in literary works still faces many obstacles, particularly when the source text contains cultural realia with no direct equivalent in the target language. This study aims to analyse the translation techniques used by three translators in rendering cultural terms and expressions in the novel The Old Man and the Sea, and to assess the quality of the translations in terms of accuracy, acceptability, and readability. The study uses a descriptive qualitative approach with a case study design, focusing on one source novel and three Indonesian translations. The research data included all cultural terms in the book, their translations, and quality assessments from six raters purposively selected. Data collection was conducted through document analysis, questionnaires, and focus group discussions, while data analysis followed the stages of domain analysis, taxonomy, component analysis, and cultural themes. The results show that the three translators utilised a combination of established equivalents, borrowing, generalisation, explicitation, paraphrasing, addition, omission, adaptation, and variation techniques, with differences in the intensity and combination of techniques used. These findings confirm that translation techniques influence how the source culture is represented in the target text and the quality of the resulting translation. Implicitly, this study provides a theoretical basis and practical guidelines for translators in handling cultural terms, while also opening up space for the development of translation technique models in cross-cultural literary studies.